…Even correctional institutions are not safe’: a qualitative study of campus secret cults/cultism among selected inmates in a custodial centre - Nnama, Macpherson Uchenna (International journal of law, crime and justice, 2022)
The violent crime of campus cultism is widespread in Nigeria and hence has attracted increasing policy attention and scholarly works. However, much of the literature has focused on cultists (perpetrators of cultism) in the free world—cultism among prison inmates has been largely underexplored. Therefore, this study uniquely examined the importation and subsistence of cults/cultism in Abakaliki custodial centre, Nigeria. Following a cross-sectional research design, snowballing and purposive sampling techniques were used to recruit 24 cultists, who participated in the in-depth oral interviews. Findings revealed that the campus secret cult tradition has crept into the correctional institution, where is perpetrated and perpetuated to attenuate the ‘pains of imprisonment’ and for survival (coping strategies) and adaptation (adjustment patterns). The problem has serious implications for prison security and reforms by frustrating treatment efforts. There is persistent desocialisation, manipulation and brainwashing of inmates through social contamination and learning of criminal thought patterns and hazing. Most of the activities of cultists are deeply shrouded in secrecy and regular use of argots (criminal jargons/slangs/coded languages) is widespread. The goal is to beat security and uphold group solidary, identity and proselytisation at all time and location, regardless of the associated risks and threats. Obtaining firsthand information in order to gain deeper insights into the modus operandi of cultists in the prison system promises a successful reformation of inmates and their reestablishment/reintegration upon release, which adds to increase custodial and public safety.